Land Procurement for Infrastructure Projects under the Job Creation Law - Abdul Kadir Jaelani (Contrarius, 2025)
Indonesia has enacted a regulation on land acquisition for public purposes through the Job Creation Law, aiming to accelerate infrastructure development. However, a critical question arises as to whether the law effectively ensures justice for the affected communities. This study aims to analyze the legal implications of the Job Creation Law on land procurement for infrastructure projects, with a particular focus on its ability to balance public interest and individual rights. Employing normative legal research, this study is based on the analysis of secondary data, including primary, secondary, and tertiary legal materials. The findings reveal that while the regulation provides a legal framework for land acquisition with compensation mechanisms, it often leads to disputes between the government and affected communities due to conflicting interests. Furthermore, several challenges hinder the implementation of land acquisition, such as incomplete planning documents, inadequate permits, and inconsistencies in development plans. In conclusion, although the law promotes development, its implementation must be improved to better ensure fairness, legal certainty, and public justice.